Comparison of Preoperative Quantitative Magnetic Resonance Imaging and Clinical Assessment of Deep Pain Perception as Prognostic Tools for Early Recovery of Motor Function in Paraplegic Dogs with Intervertebral Disk Herniations. (25th April 2017) - Wang‐Leandro, A.; Siedenburg, J.S.; Hobert, M.K.; Dziallas, P.; Rohn, K.; Stein, V.M.; Tipold, A.
Abstract : Background: Prognostic tools to predict early postoperative motor function recovery (MFR) after thoracolumbar intervertebral disk herniation (IVDH) in paraplegic dogs represent an opportunity to timely implement novel therapies that could shorten recovery times and diminish permanent neurological dysfunctions. Hypothesis: Fractional anisotropy (FA) values obtained using diffusion tensor imaging have a higher prognostic value than a lesion extension ratio in T2‐weighted images (T2W‐LER) and clinical assessment of deep pain perception (DPP) for MFR. Animals: Thirty‐five paraplegic dogs with diagnosis of acute or subacute thoracolumbar IVDH. Methods: Prospective, descriptive observational study. At admission, absence or presence of DPP, T2W‐LER, and FA values was evaluated. MFR was assessed within 4 weeks after decompressive surgery. Values of T2W‐LER and FA of dogs with and without MFR were compared using t ‐tests. All 3 methods were evaluated for their sensitivity and specificity as a prognostic factor. Results: No differences were found between groups regarding T2W‐LER. FA values differed statistically when measured caudally of lesion epicenter being higher in dogs without MFR compared to dogs with MFR ( P = .023). Logistic regression analysis revealed significance in FA values measured caudally of the lesion epicenter ( P = .033, area under the curve = 0.72). Using a cutoff value of FA = 0.660, the technique had a sensitivity of 80% and a specificity of 55%. Evaluation of DPP had a sensitivity of 73.3% and specificity of 75% ( P = .007). Conclusions and Clinical Importance: Evaluation of DPP showed a similar sensitivity and a better specificity predicting early MFR than quantitative magnetic resonance imaging.